2019
DOI: 10.5114/amsad.2019.83508
|View full text |Cite
|
Sign up to set email alerts
|

Is the presence of left atrial diverticulum associated with recurrence in patients undergoing catheter ablation for atrial fibrillation?

Abstract: Introduction Catheter ablation (CA) for atrial fibrillation (AF) has been a major cornerstone in the management of AF. Despite promising advances in CA techniques, long-term results reveal a high rate of recurrence after the procedure. Left atrial diverticulum (LAD), a common anatomic variant of the left atrium, was previously shown to be associated with increased risk of thrombus formation, cardiac perforation and arrhythmia. In this study we aimed to investigate the relationship between LAD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The distribution of factors potentially related to thromboembolic risk (comorbidities, LA diameter, persistent form of AF) was well balanced between the groups (Table I). Arterial hypertension was the most frequent comorbidity in all groups, which is consistent with other observations regarding the AF population [23][24][25][26][27]. The ablation procedure was performed with irrigated radiofrequency point-by-point technique (RF group) in 24 patients, and with 3 different single-shot techniques: a non-irrigated duty-cycled phased-RF catheter (PVAC) in 46 patients, a second-generation cryoballoon (CB) in 24 patients and with an irrigated multipolar RF catheter (nMARQ) in 10 patients.…”
Section: Study Populationsupporting
confidence: 91%
“…The distribution of factors potentially related to thromboembolic risk (comorbidities, LA diameter, persistent form of AF) was well balanced between the groups (Table I). Arterial hypertension was the most frequent comorbidity in all groups, which is consistent with other observations regarding the AF population [23][24][25][26][27]. The ablation procedure was performed with irrigated radiofrequency point-by-point technique (RF group) in 24 patients, and with 3 different single-shot techniques: a non-irrigated duty-cycled phased-RF catheter (PVAC) in 46 patients, a second-generation cryoballoon (CB) in 24 patients and with an irrigated multipolar RF catheter (nMARQ) in 10 patients.…”
Section: Study Populationsupporting
confidence: 91%
“…The main difference to our study is that two different types of ablation procedures were used (cryoballoon- and radiofrequency ablation) and the amount of rAF was significantly higher in the group that underwent radiofrequency ablation. Therefore we only included patients that underwent laser pulmonary vein isolation to avoid this possible bias [ 33 ]. However, none of these studies could prove LAD an independent risk factor for rAF.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, some authors have observed that LAA volume (larger than 8.8ml according to Zheng et al, and >9.99 ml by Du et al) increases the likelihood of AF recurrences after antral RF ablation [40,41]. Furthermore, Patel et al and Demir et al demonstrated that 30,4% of all patients that underwent CT scan before ablation procedure had atypical left atrial anatomy (diverticula or accessory appendages) [42,43] (Fig. 2), while the wall of the left atrium diverticula (LAD) was much thinner than that of adjacent LA (0.89±0.46 versus 2.39±0.83 mm).…”
Section: Left Atrial Appendagementioning
confidence: 99%